Experimental investigation of ventilation effectiveness and dispersion of tracer gas in aircraft cabin mockups - Patel, Jignesh Arvind (Kansas State University, 2017)
The 2015 Airline Traffic Data released by the Bureau of Transportation Statistics (BTS 2016), shows that the commercial flights serving the United States carried an all-time high of 895.5 million passengers in 2015, which represents an approximate 5 % increase in number of passengers from 2014. There is a potential for disease and/or contaminants spreading throughout the airliner cabin raising health risks for passengers and crewmembers onboard flight. In order to limit health risks caused by spread of disease and/or contaminants, it is necessary to understand the various factors affecting the airliner cabin environment. Ventilation effectiveness is one such factor investigated in this study. In addition, experiments were conducted using tracer gas to study the dispersion of tracer gas inside an airliner cabin. Experimental investigations were carried out inside a wide body, eleven-row Boeing 767 mockup cabin and a narrow body, five-row Boeing 737 mockup cabin. The Boeing 767 mockup cabin was constructed with actual aircraft components for air distribution to represent a real aircraft cabin, while the Boeing 737 mockup cabin is a fuselage section from an actual Boeing 737 aircraft. Thermal manikins occupied each seat of both the cabins to simulate thermal load from an average seated person. Four sets of experiments were conducted to evaluate the ventilation effectiveness and dispersion of tracer gas inside the aircraft cabin mockups. The first set of experiments investigated the ventilation effectiveness in a Boeing 767 mockup cabin. The second set of experiments determined the ventilation effectiveness at various heights and locations in a Boeing 737 mockup cabin. The third set of experiments focused on the study of dispersion of tracer gas inside a Boeing 737 mockup cabin with ventilation air. The last set of experiments aimed to study the dispersion of tracer gas inside a Boeing 737 mockup cabin with no ventilation air. The ventilation effectiveness studies were performed by using Carbon Dioxide (CO₂) as a tracer gas and applying the tracer gas decay method. The conclusion for the first set of experiments was that air is efficiently and uniformly supplied to all seat locations inside the Boeing 767 mockup cabin with no clear patterns with respect to seat locations, i.e. window versus center versus aisle observed. From the second set of experiments, it was concluded that the ventilation effectiveness is uniform throughout the Boeing 737 mockup cabin irrespective of seat locations and elevations from cabin floor. In order to determine the spread of disease and/or contaminants, a mixture of CO₂ and Helium (He) was used as a tracer gas. Tracer gas was released from particular locations inside the cabin to simulate gaseous contaminants released by a passenger and sampled at various locations throughout the cabin. The third set of experiments revealed that transport of tracer gas inside an aircraft cabin depends on the source location as well as on the relative distance of the sampling point from the source. Dispersion of tracer gas in the longitudinal direction was also observed inside the cabin. From the fourth set of experiments, it was concluded that even in the absence of ventilation air, considerable dispersion of tracer gas occurred in both the longitudinal and lateral directions.
Keywords: Ventilation effectiveness; Airliner cabin environment; Tracer gas technique; Experimental research; Dispersion study